Analisis saluran pemasaran ikan teri kering Di Desa Tanjung Pinang Kecamatan Kusambi Kabupaten Muna Barat - Fitri; La Ola, La Onu; Budiyanto; Sriwulan, Desy; Afyudi, Bobby (Universitas Halu Oleo, 2024)
This research was conducted in Tanjung Pinang Village, Kusambi District, West Muna Regency during January 2023. This research aims to determine marketing channels, the cost of goods sold, marketing margins and profits for dried anchovies. The population of this study was 6 dried anchovy traders. The sampling method uses the census method. The number of samples of traders used was 6 people. Observed variables include sales volume, purchase price, selling price and marketing costs. The data analysis used is marketing channels which are analyzed descriptively, the cost of goods sold is calculated using the formula HPP = TC/Q while the marketing margin is calculated using the equation M = He – Hp and profit π = TR-TC. The research results show that there are 2 marketing channel patterns for dried anchovies, namely channel I from producers to marketers I/retailers then to consumers while channel II is from producers to marketers II/collectors then to inter-island traders. The cost of selling dried anchovies to marketing actors I/retailers is lower than to marketing actors II/collectors which is higher. The marketing margin in channel I from producer to marketer I/retailer to consumer has a lower margin, while marketing channel II from producer to marketer II/collector then to inter-island traders is higher. The profits of marketing actors to marketing actors I/retailers are lower and the profits of marketing actors to marketing actors II/collectors are higher. Based on the results of research conducted in Tanjung Pinang Village, Kusambi District, West Muna Regency, it can be concluded that marketing channel II is more profitable than marketing channel I.